Design aspects of high voltage transmission line - Jabbar Qasim Fahad; Riyadh Kamil Chillab (Bulletin of Electrical Engineering and Informatics, 2020)
The transmission lines are very important in the transmitted of electrical power, and the process of selecting the voltage of the line is an important task in the design and implementation process. The process of transferring electrical power from one side then onto the next place for long away. While maintaining the percentage regulation within the permissible limits is an important problem in the transfer of energy. In electrical transmission line there are important elements are resistance, inductance and capacitance. The purpose of this paper is to study and calculate economic high-tension voltage and selection of overhead line conductor ACSR.